Analisis Niat Beli Produk Herborist terhadap Influencer Marketing dan Ulasan Konsumen Online - Rita Haju Kaesti; Agus Suyatno; Esti Dwi Rahmawati (Jurnal Kewirausahaan Cerdas dan Digital, 2024)
This research aims to analyze the influence of influencer marketing on purchase intentions through online consumer reviews. The population in this study were users of herbalist products. The number of samples used in this research was 100 respondents. The variables used in this research are influencer marketing, purchase intention and online consumer reviews. The data used in this research are primary data and secondary data. The data collection method used was a questionnaire. The data processing technique in this research uses SmartPLS 4.1. The results of this research show that influencer marketing has a positive and significant effect on online consumer reviews, influencer marketing has a positive and significant effect on purchase intention, online consumer reviews have a positive and significant effect on purchase intention, influencer marketing has a positive and significant effect on purchase intention through consumer reviews on line.